MENINGKATKAN KREATIVITAS ANAK MELALUI METODE BERMAIN PLASTISIN TANAH LIAT - Maisarah, Ayu; Mahmud, Muchammad Eka; Saugi, Wildan (Journal on Early Childhood Education Research (JOECHER), 2019)
This research aims to improve the creativity skill of children at early age through play by using plasticine in the group of B2 at TK IT Salsabila Samarinda. The type of the research is classroom action research with three cycles. The aspects assessed on the children?s creativity skill are fluency, originality, flexibility and detail. The result of the classroom action research shows an improvement on the children?s creativity skill through plasticine media during the pre-cycle, cycle I, cycle II, and clycle III.  The children?s creativity skill on the pre-cycle is 9% with undeveloped or poor category and 27% on the cycle I with undeveloped or poor category. Then, on the cycle II it increases to 47% with developing or fair category and on the cycle III it becomes 93% with well-developed or very good category. It shows that play by using plasticine can improve the creativity of children at early age.